Imelda's day in court ; The politics of Lahar ; Fr. Rogliardi [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Tackles Imelda Marcos conviction in court for ill-gotten wealth; debate on the lahar scam; and interview with Fr. Pierre Rogliardi, parish priest in Las Pinas, about his program to provide decent housing for the poor in his community.
Imelda's day in court (16 min.) -- The Politics of Lahar 919 min.) -- Fr. Rogliardi (15 min.)
VHS.
Reporters, Marga Ortigas, Luchi Cruz-Valdes.
Video recording
Keywords: Marcos, Ferdinand Edralin, 1917-1989.; Marcos, Imelda Romualdez, 1929-.; Rogliardi, Pierre; Political corruption -- Philippines; Administrative responsibility -- Philippines; Social service -- Philippines